2010
DOI: 10.1177/1532673x10374170
|View full text |Cite
|
Sign up to set email alerts
|

The Lifecycle of Public Policy: An Event History Analysis of Repeals to Landmark Legislative Enactments, 1951-2006

Abstract: The first stage in the policy lifecycle-creation-has garnered significant attention while the final stage-repeal-has received scarcely any. To reconcile this imbalance, an extensive data set recording repeals to landmark laws enacted from 1951 to 2006 was complied. Event history analysis yields three significant results. First, the incidence of repeal exhibits a regular pattern characterized by an increasing hazard immediately after enactment followed by institutionalization and a monotonically declining hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…Party-line votes on significant issues suggest, though of course do not establish, more extreme redistribution. As for whether legislation adopted by unified governments is more vulnerable to repeal, although some preliminary empirical research on this point suggested the opposite (Maltzman and Shipan 2008), more recent research has found that legislation enacted under divided government is indeed more durable than legislation enacted under unified government (Ragusa 2010), which again is broadly consistent with the model's predictions (though certainly not conclusive).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Party-line votes on significant issues suggest, though of course do not establish, more extreme redistribution. As for whether legislation adopted by unified governments is more vulnerable to repeal, although some preliminary empirical research on this point suggested the opposite (Maltzman and Shipan 2008), more recent research has found that legislation enacted under divided government is indeed more durable than legislation enacted under unified government (Ragusa 2010), which again is broadly consistent with the model's predictions (though certainly not conclusive).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, consistent with the model's predictions (and unsurprisingly) repeals are more likely following a change in the partisan control of the government (Berry, Burden and Howell 2010), but-also consistent with the model's predictions-repeals are less likely during periods of divided government (Ragusa 2010). 35 35 As noted above, partisan unity or division may not correlate perfectly with the sort of unity or division that is relevant here, but it its likely somewhat correlated.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Counties drop out of the analysis after they adopt a policy. In this research the authors employ event history analysis, an analytical technique that is capable of producing meaningful results in models of rare events (Box-Steffensmeier and Jones 1997), and thus has been found useful by policy scholars studying policy adoption and policy change (Berry and Berry 1990;Hays and Glick 1997;Mintrom 1997;Ragusa 2010;Shipan and Volden 2006). Additionally, event history analyses explicitly model the effect of time and thus are more appropriate than standard regression approaches for handling serial autocorrelation that results from including covariates with correlated errors due to temporal patterns (Tabachnick and Fidell 2013).…”
Section: Modelingmentioning
confidence: 99%
“…It may be that late adopters, by building on the experiences of first adopters, achieve more effective and longlasting change (Glick and Hays 1991, p. 837). Or are new policies quickly amended (Ragusa 2010) and maybe even totally dismantled ?…”
mentioning
confidence: 99%